Network analysis of the editorial boards in management of technology and innovation journals: The network of the editors - Δανελιάν, Κωνσταντίνος (2018)
In this thesis, certain characteristics of the editorial boards of 150 journals listed in the Management of Technology and Innovation field of the SCImago Journal Rank list for 2015 are analyzed. We start by explaining the importance of the editorial boards and then we investigate them through the use of descriptive statistics. Using the members of the editorial boards we construct several networks connecting them. The characteristics of those networks (connectivity, degrees, centrality measures) are further analyzed.